2012
DOI: 10.1111/j.1468-1293.2012.01045.x
|View full text |Cite
|
Sign up to set email alerts
|

End‐stage renal disease and dialysis in HIV‐positive patients: observations from a long‐term cohort study with a follow‐up of 22 years

Abstract: ObjectivesRenal disease is a common and serious complication in HIV-infected patients. MethodsA retrospective cohort analysis for the period 1989-2010 was carried out to determine the prevalence, incidence and risk factors for end-stage renal disease (ESRD). ESRD was defined as initiation of renal replacement therapy. Three time periods were defined: 1989-1996 [pre-highly active antiretroviral therapy (HAART)], 1997 (early HAART) and 2004. ResultsData for 9198 patients [78.2% male; 88.9% Caucasian; cumulative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
53
1
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(64 citation statements)
references
References 37 publications
4
53
1
3
Order By: Relevance
“…Injected drugs use and HCV co-infection were known risk factors for ESRD in HIV-infected patients [2]. According to our results, these factors are also important determinants of a lower survival in HIV-infected patients on HD.…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…Injected drugs use and HCV co-infection were known risk factors for ESRD in HIV-infected patients [2]. According to our results, these factors are also important determinants of a lower survival in HIV-infected patients on HD.…”
Section: Discussionmentioning
confidence: 93%
“…Regardless of black patients having more advanced kidney disease at HIV diagnoses, a faster progression to ESRD [12,] and a risk of ESRD 2-6 folds higher than other races [1,2,12], black race is not a survival determinant in this studied population [3,4]. Only one group from the United Kingdom [12] found that black patients had higher survival after renal replacement therapy initiation when compared to other races (5-year survival of 85.2 vs. 43.4%); however, these results were not adjusted to important variables, such as age, gender, infection status, and ESRD etiology.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations